Pengelolaan SDM Dan Perencanaan Sumber Daya Manusia Dalam Kemajuan Suatu Organisasi - Jelang Ramadhan; Reyhan Alif Rachmadsyah (Lembaga Pengembangan Kinerja Dosen, 2024)
This article will discuss the importance of the role of human resource management and planning for the progress of an organization. This is based on human resources as the main key to the organization in achieving its goals. Human resources with good management will certainly be beneficial for the organization. The importance of managing and planning human resources is also based on human resources which today are often referred to as assets that need to be given training so that their abilities can continue to grow. This is because if HR does not develop, the status of assets in HR will turn into a burden for the company so that the company / organization cannot advance.